1986
DOI: 10.1002/hed.2890080312
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic salivary gland carcinoma: A clinicopathologic correlation

Abstract: Between 1960 and 1980, 71 cases of adenoid cystic carcinoma (ACC) were reviewed according to treatment modality and clinical course. Histologic review of pathologic slides was performed to classify the tumors into their predominant histologic pattern (tubular, cribriform, solid). The predominant histologic patterns of the tumors were equally divided between tubular and cribriform. Very few were classified as a solid pattern. In the patients receiving the same type of therapy (surgery and irradiation), the crib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 16 publications
1
28
0
4
Order By: Relevance
“…Several previous studies showed that advanced stage, high grade, and submandibular location were prognostic for a poorer outcome, and differences in histological features were reported to affect natural history [8,23,25,26,27,28,29]. Positive/close margins on histopathology and cT4 stage for VII nerve involvement or for involvement of other structures were the only clinical parameters at diagnosis retaining their value also at multivariate analysis (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Several previous studies showed that advanced stage, high grade, and submandibular location were prognostic for a poorer outcome, and differences in histological features were reported to affect natural history [8,23,25,26,27,28,29]. Positive/close margins on histopathology and cT4 stage for VII nerve involvement or for involvement of other structures were the only clinical parameters at diagnosis retaining their value also at multivariate analysis (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Though most cases arise in head and neck, other primary locations include breast, lung, larynx, and trachea [15]. Adenoid cystic carcinoma can invade into the neighboring structures/organs by direct extension and perineural invasion and lead to distant metastases via hematogeneous route [16,17]. Adenoid cystic carcinoma arising in the laryngo-tracheal tree can invade into the thyroid gland and clinically present as a thyroid nodule [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Adenoid cystic carcinoma occurs primarily in the major and minor salivary glands, but can also be found at other sites 2 . The disease usually presents in a localized manner, but is known for its propensity for late metastasis (up to 15 years after initial diagnosis) 3 . Although acc can be found at any age, it typically presents in the 5th decade (median age: 57.4 years), and it has a slight female preponderance (up to 60% of cases) 2 .…”
Section: Introductionmentioning
confidence: 99%